2016
DOI: 10.1002/rcs.1761
|View full text |Cite
|
Sign up to set email alerts
|

Realistic and interactive high‐resolution 4D environments for real‐time surgeon and patient interaction

Abstract: Background Remote consultations that are realistic enough to be useful medically offer considerable clinical, logistical and cost benefits. Despite advances in virtual reality and vision hardware and software, these benefits are currently often unrealised. Method The proposed approach combines high spatial and temporal resolution 3D and 2D machine vision with virtual reality techniques, in order to develop new environments and instruments that will enable realistic remote consultations and the generation of ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…The limitations of the present study include (1) Although it has been reported by some authors that the use of the 3D surgical scope improves depth perception and enhances intraoperative visualization of lesions compared with the use of the conventional 2D scope, there have been no large-scale or long-term studies published to support these findings. 17,28,29 The future availability of new technologies, such as the new platform of the Da Vinci-SP Robot (Intuitive Surgical), the new generation of the 3D high-definition laparoscopic vision system, 28 and further refinement of articulated instruments might lead to better surgical outcomes, it will be increasingly difficult to highlight any slight difference between 2D and 3D NIR-ICG.…”
Section: Discussionmentioning
confidence: 99%
“…The limitations of the present study include (1) Although it has been reported by some authors that the use of the 3D surgical scope improves depth perception and enhances intraoperative visualization of lesions compared with the use of the conventional 2D scope, there have been no large-scale or long-term studies published to support these findings. 17,28,29 The future availability of new technologies, such as the new platform of the Da Vinci-SP Robot (Intuitive Surgical), the new generation of the 3D high-definition laparoscopic vision system, 28 and further refinement of articulated instruments might lead to better surgical outcomes, it will be increasingly difficult to highlight any slight difference between 2D and 3D NIR-ICG.…”
Section: Discussionmentioning
confidence: 99%
“…Also, the resolution is very low (1268 × 720) and the integration of artificial intelligence does not make any difference. References 39,41,43,44,47,48,79,and 86‐89 used different screens, PCs, or monitors to view the data along with other devices like iPad, projectors, and camera. Different from all these, Zhao et al 9 used a glasses‐free polyhedron‐shaped display device for telesurgical guidance.…”
Section: Discussionmentioning
confidence: 99%
“…Although VR technology has been applied in clinical applications such as surgery 22,23,56 , the insufficient spatial and temporal resolution of magnetic resonance imaging (MRI) and computed tomography (CT) has limited the uncovering of underlying physiological mechanisms of moving structures in live animal models 58,62 . In this context, we sought to address the temporal dependence of structural deformations to recapitulate the dynamics of developmental cardiac physiology.…”
Section: Introductionmentioning
confidence: 99%